2019
DOI: 10.1002/bin.1666
|View full text |Cite
|
Sign up to set email alerts
|

Training behavioral technicians to implement naturalistic behavioral interventions using behavioral skills training

Abstract: Training behavioral technicians mainly focuses on teaching accurate implementation of structured behavioral intervention programs. Often behavioral technicians are unable to adequately promote their clients' learning in less structured environments, which can limit opportunities for generalization of the clients' skills to the natural environment. The aim of the present study was to evaluate the effectiveness of using behavioral skills training to coach behavioral technicians on the implementation of naturalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…A limitation of the present study is the absence of child measures. Without this data, it is unclear as to whether increases in therapists' fidelity of implementation resulted in any changes in child behavior (Jimenez‐Gomez et al, 2019). Future research on therapist training should include child measures to determine whether increases in therapist fidelity lead to better child outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…A limitation of the present study is the absence of child measures. Without this data, it is unclear as to whether increases in therapists' fidelity of implementation resulted in any changes in child behavior (Jimenez‐Gomez et al, 2019). Future research on therapist training should include child measures to determine whether increases in therapist fidelity lead to better child outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Ninety percent of studies (n = 18) implemented all BST components as a complete training package, while 10% of studies (n = 2) implemented instruction as a separate phase in the research design (Hogan et al, 2015;Nabeyama & Sturmey, 2010). Ninety percent of studies (n = 18) reported percentage of correct responses as the primary dependent variable, while one study reported percentage of positive interactions as the primary dependent variable (Jimenez-Gomez et al, 2019), and one study reported rate-per-minute of staff behavior as the primary dependent variable (Melendez et al, 2020). Examples of measured outcomes from specific studies included percentage of correct responses for DTT, percentage of steps implemented correctly in a reading racetrack intervention, percentage of steps performed correctly in a NLP intervention, and percentage correct implementation of response interruption and redirection (RIRD) for stereotypy.…”
Section: General Intervention Characteristicsmentioning
confidence: 99%
“…Generalization was assessed in 45% (n = 9) of studies and was scored based on author-provided definitions of gen- Maintenance was assessed in 45% (n = 9) of studies and was scored based on author-provided definitions of maintenance. Of those studies that assessed maintenance, 89% (n = 8) had sufficient overall quality/rigor and outcome ratings for their maintenance findings to be interpreted with confidence (see Figure 4; Aherne & Beaulieu, 2019;Davenport et al, 2019;Hassan et al, 2017;Homlitas et al, 2014;Jimenez-Gomez et al, 2019;Melendez et al, 2020;Nabeyama & Sturmey, 2010;Palmen et al, 2010). Three out of nine studies received scores indicating that maintenance data were collected at least 1 week, but less than one month after intervention was completed.…”
Section: Generalization and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral skills training (BST) is an established, evidencebased staff training methodology (Sarokoff & Sturmey, 2004;Jimenez-Gomez, McGarry, Crochet, & Chong, 2019). BST consists of instructions, modeling, rehearsal, and feedback (Himle et al, 2004).…”
mentioning
confidence: 99%